SIFAT ORGANOLEPTIK DAN KADAR AIR KUNING TELUR ASIN ITIK MAGELANG DENGAN PENAMBAHAN EKSTRAK KAYU SECANG (Caesalpinia sappan L.) - Yayan Triono; Nur Hidayah; Mohamad Haris Septian (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2022)
Eggs are high protein and fat livestock products which makes them easily damaged. One of methods to maintain egg quality are by processing them into salted eggs with the addition of Secang wood extract (Caesalpinia sappan L.) as a natural preservative. This study aims to utilize and determine the best concentration of Secang wood extract in increasing the organoleptic properties and reducing the water content of the salted egg yolk of Magelang duck. The method used was Completely Randomized Design (CRD) with 4 treatments of different concentrations of Secang wood extract (0; 2.27; 4.44; and 6.52%) and 5 replications. Each replication contains 4 Magelang duck eggs. Data collected were analyzed by means of variance (ANOVA) at a significance level of 5% and significant differences between treatments were analyzed by Duncan. The results showed that the addition of 4.44−6.52% Secang wood extract were significantly reduced the aroma to slightly fishy (2.82−2.83), but the addition of Secang wood extract 6.52% had no significant effect on the color, which was orange (2.97−3.21), slightly salty texture (2.86−3.23), flavorless salty taste (2.20−2.52), and has not been able to reduce the water content (29.39−34.60%) of salted egg yolk Magelang duck. The conclusion of this research is that the addition of Secang wood extract to a concentration of 6.52% can reduce the fishy aroma, but has not affected the color, texture, taste, and water content of the salted egg yolk of Magelang duck. Keywords : magelang duck salted egg, organoleptic test, secang wood extract, water content